Local Government Administration and the Challenges of Primary Health Care Management in Vandeikya, Nigeria - Peter, Iorhemen Iorchir; Twar, Orkume Sylvester (Kashere Journal of Politics and International Relations, 2023)
This paper examined the management of primary health care in Nigeria with particular interest to Vandeikya Local Government Area of Benue State Nigeria. The objectives of this study are to ascertain how motivation and remuneration affected health care personnel in primary health care management in Vandeikya Local Government Area and to as well find out how health facilities constrained primary health care management in Vandeikya Local Government Area.The instrument employed by the writers was literature review and physical survey of primary health facilities, while the theoretical justification of the paper is anchored on structural functionalism theory. The finding revealed that Vandeikya Local Government Area is running her primary health care service delivery in non-compliance with minimum standard, the available health workers are unequally distributed to various health facilities, primary health centres are under-staffed and ill equipped and, finally the health education unites were being under utilized for proper education, mobilization, monitoring and evaluation of all health activities. The study recommended that, significant and adequate proportion of income at all level of government should be committed to the health sector development, local government should be more inward-looking and aggressive in the area of internally-generated revenue,priority should be given to improved living condition of the people and, there should be adequate and equipped health facilities to all communities in the local government area.